Systems of general grants for local governments in selected EU countries against the background of the general theory of fiscal policy - Alicja Sekula; Joanna Smiechowicz (Institute of Economic Research (IER), 2015)
Fiscal policy, including its expenditure aspect, is often discussed and analysed from a variety of angles in the literature on public finances, undoubtedly due to the major importance of this topic. However, not all areas of the expenditure part of fiscal policy have been subjected to in-depth analysis. One of the less discussed tools of fiscal policy consists of general purpose transfers, which are a certain type of expenditure passed from the central budget to local governments. This study focuses on presenting the systems for subsidising sub-national governments in selected European countries and evaluating, based on a synthetic measure, the fiscal policies of France, Italy, the Netherlands, Lithuania, Poland and Finland implemented by means of general transfers, with the aim of identifying the best fiscal policy with respect to subsidising and the characteristic features determining its success. The method of unitisation of statistical feature values was employed in this study to enable comparative analysis. As suggested by the results of the analysis, spanning the years 2003-2012, the highest-ranked fiscal policy implemented via general-purpose transfers has been developed in the Netherlands.
Keywords: H71; H50; H61; H30; 330; fiscal policy; general grants; European Union; central government expenditures; public finance